The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1523/jneurosci.5256-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Conditioned Stimulus Pathway Phosphoprotein 24 Expression Blocks the Reduction in A-Type Transient K+Current Produced by One-TrialIn VitroConditioning ofHermissenda

Abstract: Long-term intrinsic enhanced excitability is a characteristic of cellular plasticity and learning-dependent modifications in the activity of neural networks. The regulation of voltage-dependent K ϩ channels by phosphorylation/dephosphorylation and their localization is proposed to be important in the control of cellular plasticity. One-trial conditioning in Hermissenda results in enhanced excitability in sensory neurons, type B photoreceptors, of the conditioned stimulus pathway. Conditioning also regulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Neuronal excitability can be enhanced by closing large-conductance Ca 2 -activated K potassium channels (Shao et al, 1999;Traub et al, 2003;Brenner et al, 2005) or A-type potassium channels (Perez et al, 2006;Takeda et al, 2006;Wang and Schreurs, 2006), both of which are expressed in cortical neurons (Jin et al, 2000;Dong and White, 2003) and have been linked to increased bursting (Magee and Carruth, 1999;Jin et al, 2000;Traub et al, 2003;Gu et al, 2007). Interestingly, a decrease in A-type currents has been correlated with invertebrate learning (Yamoah et al, 2005) and hippocampal long-term potentiation (Frick et al, 2004). Additional experiments are underway to determine whether A-type or other potassium currents are reduced after extinction training.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal excitability can be enhanced by closing large-conductance Ca 2 -activated K potassium channels (Shao et al, 1999;Traub et al, 2003;Brenner et al, 2005) or A-type potassium channels (Perez et al, 2006;Takeda et al, 2006;Wang and Schreurs, 2006), both of which are expressed in cortical neurons (Jin et al, 2000;Dong and White, 2003) and have been linked to increased bursting (Magee and Carruth, 1999;Jin et al, 2000;Traub et al, 2003;Gu et al, 2007). Interestingly, a decrease in A-type currents has been correlated with invertebrate learning (Yamoah et al, 2005) and hippocampal long-term potentiation (Frick et al, 2004). Additional experiments are underway to determine whether A-type or other potassium currents are reduced after extinction training.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms that actin-binding proteins are able to affect the distribution of ion channels and regulate receptor trafficking in neurons. (Redell et al, 2007;Yamoah et al, 2005). Moreover, the role of the actin network in regulating the localization of ion channels is important in establishing the electrical properties of neurons (Hattan et al, 2002;Petrecca et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that Csp24 is phosphorylated by one-trial in vitro conditioning and multi-trial Pavlovian conditioning (Crow et al 1999, 2003; Crow and Xue-Bian 2000, 2003, 2007, 2010; Redell et al 2007). The depolarized shift in the activation curve of I A proposed to contribute to one-trial conditioning-dependent enhanced excitability is blocked by preincubation of sensory neurons with Csp antisense oligonucleotide (Yamoah et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…One-trial in vitro conditioning consists of pairing the CS (Light) with the application of 5-HT to the isolated nervous system. In vitro conditioning has been shown to produce multiple stages of time-dependent enhanced excitability in sensory neurons (photoreceptors), synaptic facilitation of the monosynaptic connection between sensory neurons and interneurons, and changes in protein phosphorylation (Crow & Forrester 1991,1993; Crow & Siddiqi 1997; Crow & Xue-Bian 2000, 2002, 2007, 2010; Crow et al 1996,1997,1998,1999, 2003; Yamoah et al 2005; Redell et al 2007). …”
Section: Methodsmentioning
confidence: 99%